Investment Report 2022/2023 - Key Findings - European Investment Bank (European Investment Bank, 2023)
Political strife caused by the war in Ukraine, an energy crisis and tightening credit are hitting EU firms just as they were beginning to emerge from the COVID-19 crisis. While the pandemic was a major shock, sizable policy support enabled firms to survive and transform. Relatively easy access to funding also helped them weather the crisis. Pandemic support has since been pulled back, however, and now firms are grappling with high inflation, instability and tighter credit conditions. These combined pressures are souring firms' outlook. The report provides insight into the state of the European economy and its ability to withstand these crises while also becoming greener and more digital. The analysis is based on the EIB Group's annual Investment Survey, which surveyed 13 000 firms in the European Union from April until July 2022 on their performance, investment, financing issues and challenges. These key findings, provide a short accessible summary of the main report's messages.